Analisis Nilai-nilai Profil Pelajar Pancasila dalam Novel “Tentang Kamu” Karya Tere Liye dan Relevansinya terhadap Pembelajaran Bahasa Indonesia - Danu Saputra; Nurhusna Nurhusna; Anita Candra Dewi (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to describe: 1) the values ​​of the Pancasila Student Profile contained in the novel "Tentang Kamu" by Tere Liye; and 2) the relevance of the values ​​of the Pancasila Student Profile to Indonesian language learning. The type of research used is a qualitative approach with a descriptive method. The research data comes from the novel "Tentang Kamu" by Tere Liye. The data collection technique in this study uses reading and note-taking techniques. The data analysis techniques in this study are data reduction, presentation, and drawing conclusions. The results of this study indicate that there are values ​​of the Pancasila Student Profile in the novel "Tentang Kamu". The values ​​of faith, devotion to God Almighty, and noble character, global diversity, mutual cooperation, independence, critical reasoning, and creativity. The results of the study show that the values ​​of the Pancasila Student Profile in the novel "Tentang Kamu" are represented through characterization, plot, conflict, setting, and dialogue between characters. The values ​​of faith and noble character are evident in Sri Ningsih's patient, sincere, and respectful character. Mutual cooperation (gotong royong) is evident through the social relationships between characters who help each other, while independence is reflected in the main character's struggle to survive without relying on others. Critical reasoning emerges in the process of investigating Sri Ningsih's life journey, while creativity is evident in the character's ability to find solutions to various problems. The value of global diversity is reflected in cross-cultural interactions that demonstrate tolerance and respect for differences. These findings are relevant to the Indonesian language learning outcomes for high school students in Phase F of the Independent Curriculum, as they support the strengthening of literacy and character development of students according to the dimensions of the Pancasila Student Profile.